Trastorno mixto del desarrollo del aprendizaje escolar y sus repercusiones en un niño de 12 años de edad de la Unidad Educativa Real Audiencia de Quito - Veliz Ronquillo, Nestor Hosmany (2021)
The present case study focuses on the impact of learning in a 12-year-old child based on the mixed developmental disorder of school learning, likewise this is a manifestation that is obtaining a higher impact on the psychosocial life of the child in which focuses on whether or not he has the disorder as such, in this way the development of school academic activities that appears in various areas is evidenced and the perception of stimuli that give information in these areas of reading, writing and mathematics can be appreciated . As far as possible, the methodology used begins with the observation of the patient, application of the interview and clinical history, observation and application of tests to monitor reading and writing spelling, application of children's intelligence tests (mathematical skills) and application of the battery. Psychometric House-Tree-Person projective test the latter to be able to evaluate the relationship of the origin with the problem posed where it expresses fear through the drawing of the house while in the tree it presents a closed form of affective repression and in the person it manifests problems Communication. As part of the process, a therapeutic scheme was carried out which managed to mitigate some findings of this process, having positive results with its application.